The Role of Principal As An Educator In Building A Religious Culture in Public Elementary School Number 12 Semabu District Tebo - Ai Anggraini; Sesti Novalina; Dody Putra; Diana Sari; Ilham Ilham (Sekolah Tinggi Agama Islam Taruna Surabaya, 2023)
Principals are responsible for running the wheels of their school organization. This study tries to describe the data related to the role of the principal as an educator in building a religious culture at SDN 12 Semabu, Tebo Regency. With a descriptive qualitative approach where this research aims to understand or describe phenomena or events in an in-depth and detailed way. Observation, interview and documentation techniques are the basis for data collection. The results of this study that the principal at SDN 12 Semabu Tebo Regency has been able to carry out his role as an educator or educator with several abilities, namely understanding his role as principal, supervising and carrying out his duties as an educator. Meanwhile, the principal in building a religious culture, provides religious guidance and emphasizes all Muslimah female students to wear the jilbab every day, attend Friday prayers in congregation, commemorate Islamic holidays, learn to read the Qur'an and have a noble character with a culture of greetings, and smiles as a religious culture at SDN 12 Semabu. There are students who follow other religions, of course this is the obligation of SDN 12 Semabu to follow the applicable curriculum procedures.